Cerebrosides, extracellular glycolipids secreted by the selective lignin-degrading fungus Ceriporiopsis subvermispora. (March 2017) - Nishimura, Hiroshi; Yamaguchi, Daisuke; Watanabe, Takashi
Graphical abstract: Highlights: Three cerebrosides are found in a selective lignin degrading fungus. Cerebrosides localize in an extracellular glucan matrix, sheath. Stable isotope 13 C and 15 N labeling experiments to cerebrosides. Structural analysis of 15 N labeled cerebrosides by CID MS/MS spectra. Abstract: Ceriporiopsis subvermispora is a selective white-rot fungus that degrades lignin at a site far from the hyphae and extracellular enzymes, without intensive damage to the cellulose. In selective ligninolysis, low molecular mass metabolites play a principal role and amphipathic substances are involved to control the degradation and transport of hydrophobic aromatic molecules, including lignin and lipids; however, secretion of the amphipathic substances by this fungus has not been well understood, except for alk(en)yl itaconates called ceriporic acids, which have a weak amphiphilicity. Herein, we report for the first time that the fungus secretes cerebrosides that are classified as glycosphingolipids. By using liquid chromatography electron spray ionization mass spectrometry (LC-ESI–MS) and nuclear magnetic resonance (NMR) spectroscopy coupled with stable isotope feeding experiments with 13 C-glucose and 15 N -ammonium sulfate, the cerebrosides were determined to be N -hydroxyoctadecanoyl-1- O -β-d -glucopyranosyl-4 E, 8 E -sphingadienine, N -hydroxyoctadecanoyl-1- O -β-d -glucopyranosyl-4 E, 8 Z -sphingadienine, and N -hydroxyoctadecanoyl-1- O -β-d -glucopyranosyl-9-methyl-4 E, 8 E -sphingadienine. The cerebrosides are strong amphipathic substances and potential metabolites for regulating difference and symbiosis within the microbial community.